The Synthesis of Hydrocarbons for Fuel and Lubricants via Ceramic Membrane Reactor. (13th April 2015) - Mosby, James M; McGuire, Patrick; Taggart, Daniel; Staley, Jacob; Elangovan, S
Abstract : The development of alternative feed stocks for fuels and chemicals has received growing interest as a means to reduce greenhouse gas (GHG) emissions. Biomass has been proposed and used as one alternative that is converted to fuels and chemicals using high energy reactions that require catalyst and/or hydrogen. To have a significant market penetration and corresponding reduction in GHG, biomass fuels and chemicals need to compete economically with petroleum feed stocks. Thus, Ceramatec is developing a novel technology that uses a ceramic membrane reactor to reduce the cost of converting biomass derived free fatty acids (FFAs) to infrastructure compatible hydrocarbons. This work has centered on improving the selectivity and efficiency of the electrolysis by using a NaSICON membrane to customize the anolyte specifically for the oxidation reaction.